ANALYSIS OF ADEQUACY OF FUNDS, LIQUIDITY, AND CLAIM EXPENSES ON THE HEALTH OF SHARIA INSURANCE COMPANIES - Dara Almira (Inovbiz: Jurnal Inovasi Bisnis, 2021)
In this globalization era, the business world adhering to sharia principles has begun to develop, not only banking financial institutions, but non-banking financial institutions, one of which is insurance institution also has started to adopt the sharia principles. Insurance institutions must grant the best company performance so that they can be comprised in the criteria for a healthy and appropriate insurance company in paying their customers' claims. Public trust in insurance is influenced by the health of the insurance company and the accuracy of insurance in paying claims. One way to assess the health condition of an insurance company is to use Return on Equity.Return on Equity at PT AIA Financial was still below the unsafe percentage because almost all the percentage of Return on Equity had been below 40%. Therefore, it was important to know what things influenced Return on Equity so that Return on Equity of PT. AIA Financial could be able to be in a safe spot. Furthermore, the way to observe the financial performance of an insurance company required to calculate the level of adequacy of funds, liquidity, and claims expense in advance. The research was aimed at determining the influence of the Adequacy of Funds, Liquidity, and Claims Expenses toward Company's Health Level which was projected in Return On Equity. The research methods applied in the research were descriptive and associative. The result of the research shows that the Adequacy level of Funds does not influence Return On Equity. Meanwhile, Liquidity and Claims Expenses does influence Return On Equity.